W.H. Auden's "The healing fountain" read through A. Aviram's theory of poetic rhythm - Laarif, Boutheina Boughnim (Cambridge Scholars Publishing, 2017)
Although Auden has often been hailed as the twentieth century's master of metre and most outstanding practitioner of traditional poetic forms, his metrical art still remains a mystery, as far as its real significance is concerned. This book sheds new light on the enticing appeal of formal poetry which induced Auden into composing in almost every possible stanza form. In order to work out a 'new' appreciative assessment of Auden's formal art, the book uses Amittai Aviram's theory of poetic rhythm, which transcends the common literary critical process, based on the rhetorical assessment of rhyth.